Evidence for a new fumarate hydratase gene mutation in a unilateral type 2 segmental leiomyomatosis. - Parmentier, L; Tomlinson, I; Happle, R; Borradori, L (2010)
BACKGROUND: Multiple cutaneous and uterine leiomyomata syndrome (MCUL; MIM 150800) is a rare condition that sometimes predisposes to renal cancer. It is caused by deleterious mutations in the fumarate hydratase (FH) gene. In many patients, skin leiomyomas have been reported to develop according to a segmental type 1 or type 2 distribution. We report a patient showing multiple leiomyomas distributed according to a segmental type 2 distribution and covering several areas exclusively on the left side of his body. OBJECTIVE: To search for a specific mutation in the FH gene associated with this phenotype. METHODS: Genomic DNA from peripheral blood leucocytes of the proband was sequenced and screened for mutation of the FH gene. RESULTS: Heterozygosity for an as yet undescribed mutation c.695delG, leading to a truncated protein p.Gly232AspfsX24, was found. CONCLUSION: We report a new mutation in the FH gene and discuss the unusual pattern of purely unilateral distribution in the present case.